The early Neolithic in Greece: The first farming communities in Europe - Perlès, Catherine (Cambridge University, 2013)
Farmers made a sudden and dramatic appearance in Greece around 7000 BC, bringing with them domesticated plants and animals, new crafts and techniques, and establishing settled villages. They were Europe's first farmers, but Catherine Perles argues that the stimulus for the spread of agriculture to Europe was a maritime colonisation movement involving small groups of people of various origins. With title competition